Economic Valuation of Mangrove Restoration in Indonesia - Djoko Suprapto; Mayanggita Kirana; Indah Susilowati; Akhmad Fauzi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2015)
Mangrove forest is one of the important ecosystems in Karimunjawa, Indonesia. It provides a variety of services both ecologically and economically. However, over-exploited activity, such as timber theft, can be threatening the sustainability of mangrove forest in Karimunjawa now and in the future. Thus, the improved management for mangrove forest is necessary to ensure its sustainability, and it is depending on how people value the conservation from economic and environment consideration. This study examines the factors influencing on the willingness to pay (WTP) of respondents for mangrove restoration in Karimunjawa. A total of 502 respondents were interviewed using census method. The method employed is Contingent Valuation Method (CVM)Single Bounded. In CVM, the logit model was defined based on dichotomous choice method to estimate the willingness-to-pay (WTP) randomly with three different starting bid value. Findings showed that local awareness of the importance of the values given by mangroves was popularized among local communities. The findings also indicated that respondents who are higher education and have more income were more likely to pay for the mangrove restoration.